Numerical study of tidal effect on the water flux across the Korea/Tsushima Strait - Jiang, Wenxin; Yang, Dezhou; Xu, Lingjing; He, Zhiwei; Cui, Xuan; Yin, Baoshu (Frontiers in Marine Science, 2023)
Tremendous amounts of materials and energy are transported from the East China Sea (ECS) to the East/Japan Sea (JSEJS) through the Korea/Tsushima Strait (TUSKTS).2 Tides undoubtedly play an important role in regulating ocean circulation on the broad continental shelf of the ECS, while the effects of tides on the water exchange between the ECS and JSEJS remain unclear. Using a three-dimensional Regional Oceanic Modeling System (ROMS) circulation model, we conducted numerical experiments with tides, without tides, and only barotropic tides. The results showed that the water flux across the TUSKTS can increase by up to 13% (in summer) when excluding tides from the numerical simulation. To understand how tidal forcing regulates the TUSKTS water flux, we performed a dynamic diagnostic analysis and revealed that the variation in sea surface height under tidal effect is the main reason for the water flux variation across the TUSKTS. The tidal effect can adjust the sea surface height, weaken the pressure gradient and reduce the water flux across the TUSKTS, which affect the intensity of water exchange between the ECS and JSEJS. The tidal effect can alter sea level difference between the Taiwan Strait and the TUSKTS, which influences the TUSKTS water flux. Tides can also influence the TUSKTS water flux by altering the sea surface height through interaction with topography and stratification. We also found that tidal effect weakens the northward intrusion of the Yellow Sea Warm Current in winter and in turn enhances the water flux across the TUSKTS according to volume conservation. These modeling results imply that tides must be considered when simulating the ocean environment of the northwestern Pacific Ocean.